2019
DOI: 10.1038/s41419-019-1989-z
|View full text |Cite
|
Sign up to set email alerts
|

Verteporfin-induced lysosomal compartment dysregulation potentiates the effect of sorafenib in hepatocellular carcinoma

Abstract: Lysosomal sequestration of anti-cancer compounds reduces drug availability at intracellular target sites, thereby limiting drug-sensitivity and inducing chemoresistance. For hepatocellular carcinoma (HCC), sorafenib (SF) is the first line systemic treatment, as well as a simultaneous activator of autophagy-induced drug resistance. The purpose of this study is to elucidate how combination therapy with the FDA-approved photosensitizer verteporfin (VP) can potentiate the antitumor effect of SF, overcoming its acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 55 publications
5
48
0
Order By: Relevance
“…In addition, considering the functional interplay between Hippo and Wnt/β-catenin, we believe that VP may also be affecting the expression of genes from this pathway. Consistently, it has previously been reported that VP may enhance the effects of gemcitabine and other anti-tumor drugs by inhibiting the expression of YAP1 [46][47][48], by inhibition of autophagy [8] or modulating lysosomal activity [49]. Hence, VP has been proposed as an effective chemosensibilizing agent.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, considering the functional interplay between Hippo and Wnt/β-catenin, we believe that VP may also be affecting the expression of genes from this pathway. Consistently, it has previously been reported that VP may enhance the effects of gemcitabine and other anti-tumor drugs by inhibiting the expression of YAP1 [46][47][48], by inhibition of autophagy [8] or modulating lysosomal activity [49]. Hence, VP has been proposed as an effective chemosensibilizing agent.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, it has been demonstrated that lysomotropic compounds are able to increase lysosomal pH and as a consequence decrease enzyme activity and proposed to impair lysosomal function [65]. Similar, a recent study has found that lysosomal pH increase with Verteporfin induced cell toxicity in malignant hepatocellular cells only [66].…”
Section: Discussionmentioning
confidence: 86%
“…We thus analyzed a mechanism of action that is known to be related to multiple drug resistance (MDR). Lysosomal sequestration (or lysosomal drug entrapment) of anti-cancer compounds reduces drug availability at intracellular target sites, thereby limiting drug sensitivity and inducing chemoresistance [30,49]. Lysosomes mediate MDR in many cancers, such as those showing resistance to cisplatin, sorafenib, doxorubicin, and oxaliplatin [30].…”
Section: Discussionmentioning
confidence: 99%